Spektrum Pesantren di Tengah Hegemoni Modernisasi - Eman Sulaeman (Misykah : Jurnal Pemikiran dan Studi Islam, 2020)
Islamic boarding schools as educational and social institutions have a very large role in shaping the culture / culture of the community. On the other hand, the pressure for modernization, which sometimes carries negative values, also has a very large influence on the formation of community culture. The interpretation of modern values to community culture is sometimes more visible in the "ization "of pesantren values (which are identical to their religious culture) and modernization values (which are identical with their bad values). - The role of Islamic boarding schools as educational institutions in building community culture is at least seen in the educational model it implements, which emphasizes habituation or culturalization. With the charismatic nature of a kiyai as a role model for society and the culture of the pesantren and its distinctiveness, the pesantren institution has succeeded in stemming the negative values of modernization, especially those related to community morals. Abstrak Pesantren sebagai institusi pendidikan dan social memiliki peranan yang sangat besar terhadap pembentukan budaya / kultur masyarakat. Di sisi lain desakan modernisasi yang kadang membawa nilai-nilai negative, juga memberikan pengaruh yang sangat besar terhadap pembentukan kultur masyarakat. Interperensi nilai modern terhadap kultur masyarakat terkadang lebih tampak pada "isasi" nilai pesantren (yang identik dengan budaya religiusnya) dan nilai modernisasi (yang identik dengan nilai buruknya) . - Peran pesantren -sebagai institusi pendidikan- dalam membangun kultur masyarkat setidaknya terlihat pada model pendidikan yang diterapkannya yaitu lebih mengedepankan pembiasaan atau kulturalisasi. Dengan karismatik seorang kiyai sebagai role of model masyarakat serta kultur pesantren dan kekahasannya, institusi pensantren telah berhasil membendung nilai-nilai negative modernisasi terutama terkait dengan moral masyarakat